Maternal and infant health problems after normal childbirth: a randomised controlled study in Zambia. Issue 6 (June 1998) - Ransjö-Arvidson, A B; Chintu, K; Ng'andu, N; Eriksson, B; Susu, B; Christensson, K; Diwan, V K
Abstract : STUDY OBJECTIVES: The main aim of the study was to discover if a midwife home visiting programme has a significant effect on the prevalence of health problems and breast feeding behaviour of mothers who delivered normally and their healthy fullterm newborn babies, during a period of 42 days after delivery. Another aim was to compare the mothers', the midwife's, and the doctor's findings of prevalence of health problems at the end of the puerperium period. DESIGN: A randomised controlled trial was carried out. One group of mothers and their infants were randomly allocated to a home visiting group (Group A); the other group (Group B) was only visited at day 42. SETTING: The study was carried out at the University Teaching Hospital (UTH) in Lusaka, the capital city of Zambia. PARTICIPANTS: A total of 408 mothers who had a normal delivery and gave birth to a healthy fullterm infant, as assessed by the attending midwife, were randomised to two groups. Group A consisted of 208 mother/infant dyads who were visited by a midwife in their homes at days 3, 7, 28, and 42 after delivery and Group B consisted of 200 mother/infant dyads who were only visited at day 42. MAIN RESULTS: At day 42 an equal proportion (30%) of mothers in both groups perceived that they had health problems. The prevalence of infant health problems in Group B was significantly higher (p < 0.01) as perceived by mothers. There were more mothers in Group B (p < 0.01) perceiving insufficient milk production and giving supplementary feeding. At day 42, mothers in Group A (56%) took more actions than mothers in Group B (41%) to solve infant health problems (p < 0.03). In both groups the mothers' perceived own health problems, were significantly higher (p < 0.01) than those observed by the obstetrician and those observed by the midwife. The midwife found more infant health problems in Group B (p < 0.01) than in Group A and more infants with health problems in both groups compared with the paediatrician's findings (p < 0.01). CONCLUSIONS: There was a significant difference between the mothers' reported health problems and the health problems identified by the midwife and the doctors. The study shows that a midwife home visit and individual health education to mothers, reduce the prevalence of infant health problems, and enables the mother to more often take action when an infant health problem is identified. There is a need to re-evaluate the midwifery training curriculums with the intention to include more infant management care.